PERTANGGUNGJAWABAN HUKUM PEMILIK TOWER TELEKOMUNIKASI TERHADAP PEMILIK BANGUNAN ATAS TIMBULNYA KERUGIAN AKIBAT FORCE MAJEURE (STUDI PUTUSAN MA RI NO. 1144K/PDT/2012) - YOLANDA EVANS SIMORANGKIR (PREMISE LAW JURNAL, 2017)
The case in the Ruling of MA RI (the Supreme Court of the Republic of Indonesia) No.1144K/PDT/2012 started with a lease agreement of some parts of a place on the upper side of a building owned by H. Darmawan Kasim as the installation of telecommunication tower belonging to PT.Telkomsel. Darmawan Kasim claimed PT. Telkomsel to indemnify the loss incurred because the tower fell on his building, while PT.Telkomsel refused because according to them it was caused by force majeure such as earthquake striking the area. The research results revealed how to determine force majeure in a legal event i.e. by studying its elements; namely, the rented object is vanished, there is no element of debtor’s mistake (schuld) or neglect; the legal event in this case was not an event that can be predicted earlier and the debtor did not have any bad intention, they in fact have good intention when the legal event took place. The tower owner will definitely no loner be able to execute the agreement because the building has been vanished due to the earthquake. The judge’s consideration to fine the tower owner is regarded to be improper because the loss due to force majeure is not the tower owner’s risk or legal liability. Keywords : Legal Event, Force Majeure, Legal Liability